2021
DOI: 10.1002/chem.202103304
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Reactivity of a Substrate for SNAP‐Tag Expands Its Application for Recognition‐Driven DNA‐Protein Conjugation

Abstract: Recognition‐driven modification has been emerging as a novel approach to modifying biomolecular targets of interest site‐specifically and efficiently. To this end, protein modular adaptors (MAs) are the ideal reaction model for recognition‐driven modification of DNA as they consist of both a sequence‐specific DNA‐binding domain (DBD) and a self‐ligating protein‐tag. Coupling DNA recognition by DBD and the chemoselective reaction of the protein tag could provide a highly efficient sequence‐specific reaction. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Upon ligation, the bridged DNA should be a useful platform to assemble not only the pH-sensitive fluorophore as shown in this study, but also other functional molecules introduced on the DNA nanostructures previously [ 31 ]. For example, enzymes of interest can be located on the bridged DNA to encapsulate a defined number of enzymes within a nanoliposome by using the modular adaptors developed by our group [ 32 , 33 , 34 , 35 , 36 , 37 ]. The bridged ring skeleton with spatially assembled enzymes would be converted to a compartment upon the formation of liposome.…”
Section: Discussionmentioning
confidence: 99%
“…Upon ligation, the bridged DNA should be a useful platform to assemble not only the pH-sensitive fluorophore as shown in this study, but also other functional molecules introduced on the DNA nanostructures previously [ 31 ]. For example, enzymes of interest can be located on the bridged DNA to encapsulate a defined number of enzymes within a nanoliposome by using the modular adaptors developed by our group [ 32 , 33 , 34 , 35 , 36 , 37 ]. The bridged ring skeleton with spatially assembled enzymes would be converted to a compartment upon the formation of liposome.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously [ 78 ], two enzymes with different pH preferences, xylose reductase (XR) and xylitol dehydrogenase (XDH), were individually assembled on the fully open state of a 3D DNA scaffold through the modular adaptor method [ 79 , 80 , 81 , 82 , 83 , 84 ] in high loading yields. XR was genetically fused to the modular adaptor ZF-SNAP to obtain ZS-XR.…”
Section: Catalytic Enhancement Of Single Type Of Enzyme Assembled On ...mentioning
confidence: 99%
“…In our previous studies, the enzyme cascade reactions derived from D-xylose metabolic pathway were investigated on 2D and 3D DNA scaffolds. The modular adaptor method was applied to stably co-locate enzymes on scaffold with the precise control over enzyme stoichiometry and interenzyme distance [ 79 , 80 , 81 , 82 , 83 , 84 ]. ZS-XR [ 80 ] and G-XDH (adaptor GCN4 fused xylitol dehydrogenase) [ 101 ] were arranged on a three-well DNA scaffold with the alteration of interenzyme distance from 98 nm to 10 nm; it was found that the highest efficiency appeared at a distance of 10 nm, and the intermediates (xylitol and NAD + ) transferred to the downstream enzyme following the Brownian motion ( Figure 12 a) [ 80 ].…”
Section: Enhanced Efficiency Of Enzyme Cascade Reactions On the Dna S...mentioning
confidence: 99%